SUPERVISI PENDIDIKAN: DI ERA NABI MUHAMMAD, KHULAFAUR ROSYIDIN, DINASTI UMAYYAH, DAN DINASTI ABBASIYAH - Faishol, Muhammad (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Abstrak Bahasa Indonesia Keberhasilan proses pendidikan berkaitan erat dengan efektivitas supervisi. Supervisi yang optimal meningkatkan kualitas belajar mengajar, mencapai kesuksesan pembelajaran. Supervisi bukan hanya menciptakan output baik, tetapi juga menghasilkan outcome yang berdaya saing. Dalam konteks pendidikan, supervisi dilaksanakan oleh pimpinan lembaga pendidikan, di atas guru, dalam kegiatan pengawasan pekerjaan mereka. Sumentara Pendidikan Islam yang di-supervisi, mengarah pada masukan terhadap praktik guru agar sistem pendidikan dengan nilai-nilai Islam berjalan dengan baik. Pendidik menyelipkan unsur-unsur Islam untuk menciptakan anak didik intelektual dan religius. Dalam konteks ini, penulis mengembangkan makna supervisi, menggambarkan supervisor sebagai individu dengan kewenangan langsung merencanakan, merespons, dan mengontrol aktivitas kelompoknya. Teguran diberikan untuk memperbaiki proses pembelajaran di masa depan. Supervisi Pendidikan di Era Nabi Muhammad terilustrasi melalui kisah Sahabat Mu'adz, di mana Nabi memberikan teguran untuk menyesuaikan pembelajaran dengan kondisi muridnya. Era Khulafaurrosyidin menunjukkan Khalifah Umar sebagai supervisor yang menegur tindakan sewenang-wenang putra Gubernur Mesir terhadap warganya. Supervisi pada Dinasti Umayyah dilakukan oleh syaikh di tempat pembelajaran, sementara di era Abbasiyah pencapaian optimal di bidang pendidikan dengan pendekatan manajemen yang terorganisir dan perhatian khusus dari para khalifah terhadap supervisi pendidikan. Tahapan supervisi berkembang, melibatkan perencanaan kurikulum, pelaksanaan dengan pilihan mata pelajaran, dan evaluasi dengan indikator ketercapaian yang jelas. Era Dinasti Abbasiyah menciptakan berbagai lembaga pendidikan maju, meningkatkan peran supervisi untuk mengoptimalkan proses pembelajaran dan pengembangan pendidikan. Kata Kunci: Supervisi; Pendidikan; Optimalisasi; Pembelajaran; Evaluasi. Abstract English Languange The success of the education process is closely tied to the effectiveness of supervision. Optimal supervision enhances the quality of teaching and learning, leading to successful educational outcomes. Supervision goes beyond creating good outputs; it generates high-quality outcomes. The term "supervision" originates from English, combining "super," meaning above, and "vision," meaning to see. In the educational context, supervision is carried out by supervisors and school principals, positioned above teachers, overseeing their work. Islamic Education Supervision aims to direct the performance of educators to improve Islamic-based learning systems in specific subjects. Educators incorporate Islamic elements to create intellectually and religiously inclined students. In this context, the author develops the meaning of supervision, portraying the supervisor as an individual with the authority to plan, respond to, and control group activities directly. Corrections are given to enhance the future learning process. Supervision in the era of Nabi Muhammad is illustrated through the story of Sahabat Mu'adz, where Nabi provides guidance to adjust teaching to the students' conditions. The era of Khulafaurrosyidin showcases Khalifah Umar as a supervisor reprimanding the arbitrary actions of the son of the Governor of Egypt against the citizens. Supervision during the Umayyad Dynasty was carried out by a sheikh within educational institutions, while the Abbasid Dynasty reached the pinnacle of progress with an organized management approach and special attention from the caliphs to educational supervision. Supervision stages evolved, involving curriculum planning, implementation with subject choices, and evaluation with clear achievement indicators. In the Abbasid Dynasty era, numerous advanced educational institutions were established, enhancing the role of supervision to optimize the teaching and development of education. The stages of supervision development encompassed clear curriculum planning for elementary and secondary education. During this period, besides offering various subject choices, including core and elective subjects, the evaluation process also included clear achievement indicators. Keywords: Supervision; Education; Optimization; Learning; Evaluation.